Long-Term Resolution of Perifoveal Exudative Vascular Anomalous Complex after Intravitreal Injections of Anti-Vascular Endothelial Growth Factor - Torrell-Belzach, Nuria; Miere, Alexandra; Souied, Eric; Cohen, Salomon Y. (Case reports in ophthalmology, 2022)
Abstract Perifoveal exudative vascular anomalous complex (PEVAC) is a perifoveal aneurysmal vascular lesion found in healthy subjects. A 68-year-old woman was diagnosed with a typical unilateral and unifocal PEVAC lesion after extensive multimodal imaging and was treated with three-monthly intravitreal injections of ranibizumab. An immediate and complete resolution of the intraretinal fluid was observed. Visual acuity returned to 20/20 without any recurrence of the exudative signs along the 5 years of follow-up. Therefore, an initial anti-VEGF treatment with three-monthly intravitreal injections may be considered as a first-line treatment in PEVAC lesions and may result in long-term preservation of visual acuity.